2008
DOI: 10.1128/iai.01430-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Putative Cytochrome c Peroxidases of Campylobacter jejuni Involved in Promoting Commensal Colonization of Poultry

Abstract: Campylobacter jejuni is a leading cause of bacterial gastroenteritis in humans throughout the world, but infection of animals, especially poultry, results in a commensal colonization of the intestines. We previously found that a mutant lacking docA, which encodes a putative cytochrome c peroxidase (CCP), demonstrates up to a 10 5 -fold reduction in colonization of the chick cecum compared to wild-type C. jejuni strain 81-176. Predictions from genomic sequences identified CJJ0382 as a second locus in C. jejuni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…Recovery of wholecell lysates and fraction of C. jejuni strains into subcellular compartments for analysis of localization of proteins from the inner membrane, outer membrane, periplasm, and cytoplasm were performed as previously described (65). Proteins from each fraction representing equivalent cell numbers (∼200 μL of a C. jejuni culture at an OD 600 0.8) were loaded onto 10% SDS/PAGE gels and then were transferred to membranes for immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recovery of wholecell lysates and fraction of C. jejuni strains into subcellular compartments for analysis of localization of proteins from the inner membrane, outer membrane, periplasm, and cytoplasm were performed as previously described (65). Proteins from each fraction representing equivalent cell numbers (∼200 μL of a C. jejuni culture at an OD 600 0.8) were loaded onto 10% SDS/PAGE gels and then were transferred to membranes for immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…C. jejuni NCTC11168 contains one catalase (KatA), two cytochrome c peroxidases (Cj0358 and Cj0020c), and three peroxiredoxins (AhpC, Tpx, and Bcp) (34). KatA, Tpx, and Bcp have been shown to contribute, at least to some extent, to H 2 O 2 detoxification in C. jejuni (5,17), and Cj0358 and Cj0020c have been demonstrated to have peroxidase activity (11). AhpC has also been demonstrated to scavenge H 2 O 2 in E. coli (39) and likely performs a similar function in C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified 29 mutants with reduced colonization capacities and provided a foundation for more in-depth studies into potential colonization factors of C. jejuni. From this study and subsequent studies, a better understanding of C. jejuni cytochrome c peroxidases and glycosylated proteins that are involved in commensal colonization has been acquired (5,20,21).…”
mentioning
confidence: 99%